High Burden of Cardiac Disease in Pregnancy at a National Referral Hospital in Western Kenya. Issue 1 (7th February 2020) - Lumsden, Rebecca; Barasa, Felix; Park, Lawrence P.; Ochieng, Christian B.; Alera, Joy M.; Millar, Heather C.; Bloomfield, Gerald S.; Christoffersen-Deb, Astrid
Background: Cardiac disease is a leading cause of non-obstetric maternal death worldwide, but little is known about its burden in sub-Saharan Africa. Objectives and Methods: We conducted a retrospective case-control study of pregnant women admitted to a national referral hospital in western Kenya between 2011–2016. Its purpose was to define the burden and spectrum of cardiac disease in pregnancy and assess the utility of the CARPREG I and modified WHO (mWHO) clinical risk prediction tools in this population. Results: Of the 97 cases of cardiac disease in pregnancy, rheumatic heart disease (RHD) was the most common cause (75%), with over half complicated by severe mitral stenosis or pulmonary hypertension. Despite high rates of severe disease and nearly universal antenatal care, late diagnosis of cardiac disease was common, with one third (38%) of all cases newly diagnosed after 28 weeks gestational age and 17% diagnosed after delivery. Maternal mortality was 10-fold higher among cases than controls. Cases had significantly more cardiac (56% vs. 0.4%) and neonatal adverse events (61% vs. 27%) compared to controls (p < 0.001). Observed rates of adverse cardiac events were higher than predicted by both CARPREG I and mWHO risk scores, with high cardiac event rates despite low or intermediate risk scores. Conclusions: Cardiac disease is associated with significant maternal and neonatal morbidity and mortality among pregnant women in western Kenya. Existing clinical tools used to predict risk underestimate adverse cardiac events in pregnancy and may be of limited utility given the unique spectrum and severity of disease in this population.